Analysis of feasibility and advantages of multi‐source image registration using regional features. Issue 7 (23rd February 2021) - Zeng, Liang; Lu, Danwei; Zhu, Qingtao; Xing, Cheng; Yin, Junjun; Yang, Jian
Abstract: Automatic registration of multi‐source remote sensing data is a challenging task due to the high non‐linearity of radiometric differences among various data. Feature extraction is a key enabling technique in registration algorithm design. In this letter, we prove the feasibility of using extracted regional features for multi‐source image registration. In particular, regional features can be extracted through pixel‐level image classification, and existing off‐the‐shelf algorithms can be directly adopted. Experiment results demonstrate the robustness of the regional‐feature‐based registration method.